2018
DOI: 10.1002/jcp.26858
|View full text |Cite
|
Sign up to set email alerts
|

RUMI is a novel negative prognostic marker and therapeutic target in non–small‐cell lung cancer

Abstract: Recent comprehensive next-generation genome and transcriptome analyses in lung cancer patients, several clinical observations, and compelling evidence from mouse models of lung cancer have uncovered a critical role for Notch signaling in the initiation and progression of non-small-cell lung cancer (NSCLC). Notably, Rumi is a "protein O-glucosyltransferase" that regulates Notch signaling through O-glucosylation of Notch receptors, and is the only enzymatic regulator whose activity is required for both ligand-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 68 publications
0
11
0
Order By: Relevance
“…In this study, we only showed that the xylosyl extension of O-Glc glycans may be involved in the regulation of Notch receptor trafficking using an overexpression system with room for improvement, and it should be further investigated how a xylosyl extension is involved in the above-mentioned, and possibly other, biological processes in vivo. Taken together, our findings suggest the importance of protein folding and O-glucosylation on multiple cysteine-rich EGF repeats of Notch receptors and provide insights into the pathological mechanisms in POGLUT1-related human diseases [51,52,[55][56][57].…”
Section: Discussionmentioning
confidence: 57%
“…In this study, we only showed that the xylosyl extension of O-Glc glycans may be involved in the regulation of Notch receptor trafficking using an overexpression system with room for improvement, and it should be further investigated how a xylosyl extension is involved in the above-mentioned, and possibly other, biological processes in vivo. Taken together, our findings suggest the importance of protein folding and O-glucosylation on multiple cysteine-rich EGF repeats of Notch receptors and provide insights into the pathological mechanisms in POGLUT1-related human diseases [51,52,[55][56][57].…”
Section: Discussionmentioning
confidence: 57%
“…Along, these observations would seem to suggest that Lkb1 loss, via activation of the ID1 pathway, would interact with Notch in NSCLC tumors and, therefore, would render Notch activity functionally relevant in the development and progression of tumors of this subtype. In line to these findings, nonetheless, is the observation that Notch action inhibition in H1299 and A549 Kras mutant cells with γ-secretase inhibitor DAPT, alone or in combination with gemcitabine, had a marked effect in NSCLC cell viability and colony-forming potential [123], and that Rumi knockdown, globally inactivating Notch signaling in NSCLC A549 and H23 cells (both Lkb1-deficient [118,124]) results in marked anti-oncogenic exertion, including a significant reduction in cell proliferation, migration and survival [100]. These concurrent findings, therefore, would positively suggest that in the context of Lkb1 deficiency Notch is also in fact promoting tumor growth and neoplastic progression, and that it is possible that ID1 may be a cooperative factor likely releasing the otherwise oscillatory negative autoregulation of Hes1, and, therefore, further indicating that the molecular interaction between these two pathways is, in this case, indispensable.…”
Section: Notch and Nsclcmentioning
confidence: 99%
“…In this respect, it is important to mention that pharmacological or genetic inactivation of Notch alone has been shown to have an epistatic effect to both Kras G12D and Kras G12V mutations [87,88]. Furthermore, genetic silencing of Rumi, which regulates both ligand-dependent and -independent Notch activity [155,156], caused marked cell proliferation decrease and cell cycle S-phase arrest in both Kras G12S A549 cells and Kras G12C H23 cells [100].…”
Section: Therapy Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Diminished stemness markers, reduced resistance miR-223 [90] Upregulated; leads to overactivation of Notch Reduced CD44+ subpopulation of CSCs, improved response to erlotinib Rumi, protein-O-glucosyltransferase [91] Two to three-fold higher expression in NSCLC Knockdown led to decreased Hes1, Hey1, cell proliferation and migration induced EMT by binding to miR-137 and thus reversed the effects of Notch downregulation [83]. Several other novel pathway mediators along with their role in Notch pathway signaling and the results of their pharmacological targeting are presented in Table 2.…”
Section: H460 Cellsmentioning
confidence: 99%